PENGARUH HARGA, KUALITAS PELAYANAN DAN CITA RASA TERHADAP LOYALITAS PELANGGAN (Studi pada Cafe Siji Roso Alasmalang Banyuwangi) - Hardianti, Dio Ekky (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
In the business world, decisions about product purchases are an Customer loyalty is a behavior associated with the brand of a product. Customer loyalty has an important role in a company, retaining them means improving financial performance and maintaining company viability, this is the main reason for a company to attract and retain them. The purpose of this study was to determine the effect of price, service quality and taste on customer loyalty at the cafe siji roso Alasmalang Banyuwangi. This study uses a questionnaire method and data processing using analysis of validity, reliability and multiple linear regression. Questionnaires were distributed to 130 people who were consumers of Siji Roso Café. The results showed that the results of F arithmetic > F table (114.898 > 2.68) meant that simultaneously price, service quality and taste had a significant effect on customer loyalty. And partially (t test) the results obtained t arithmetic > t table, meaning that there is an influence between the variables of price, service quality and taste on customer loyalty. Based on the Adjusted R Square value of 0.49, it means that the independent variable can explain the dependent variable of 72.6% and the remaining 27.4% is influenced by other factors outside the research model